2013
DOI: 10.1080/08957959.2012.762913
|View full text |Cite
|
Sign up to set email alerts
|

Ionic conductivity in three crystalline phases of LiBH4under pressure

Abstract: The AC electrical conductivity of LiBH 4 was investigated below 2 GPa between 1 Hz and 1.6 MHz. The high temperature phase has an ionic conductivity of up to 0.01 S cm -1 while the low temperature phases have conductivities two orders of magnitude lower. All phases show an Arrhenius behaviour with activation energies E a between 0.5 and 0.7 eV, in good agreement with earlier data except for phase III, which is found to have the highest activation energy of the phases studied. The high temperature phase has a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“…This behavior is probably due to parasitic capacitances and inductances in the measurement circuit. No minima in Z″, such as those observed in our previous study on LiBH 4 [14], were found in this work. However, the results clearly show that the low-frequency data (f < 100 Hz) give reliable values for R.…”
Section: C 60contrasting
confidence: 67%
See 4 more Smart Citations
“…This behavior is probably due to parasitic capacitances and inductances in the measurement circuit. No minima in Z″, such as those observed in our previous study on LiBH 4 [14], were found in this work. However, the results clearly show that the low-frequency data (f < 100 Hz) give reliable values for R.…”
Section: C 60contrasting
confidence: 67%
“…If both the resistance and the capacitance of the 'electrode' part are much larger than those of the sample the two arcs will be well defined and R dc can be found from the osculation point. In our earlier study on LiBH 4 [14] the continuous development from single-to double-arc plots during the transformation from the insulating to the superionic phase was very clear and we refer the reader to that work for details.…”
Section: Experimental and Analytic Methodsmentioning
confidence: 94%
See 3 more Smart Citations